'According to the Old Text': Byron and the Sacred Scriptures. Issue 2 (December 2015) - Beatty, Bernard
Abstract : This essay in its first section argues that Byron is obsessed both by the meaninglessness of history and the idea that there might be meaning hidden in that meaninglessness. He finds in the Bible, and the paradoxical dogmas of orthodox Christianity which are based on it, a mirror and paradigm of this problem. This affects not only his thinking but also the structures and styles of his writing. In the second section, I ask why, given this interest in biblical history, Byron re-uses the Bible for his quasi-mythological poems in 1821 ( The Vision of Judgement, Cain and Heaven and Earth ). I argue that it has to do with the parallel fusion between history and fiction in the Scriptures and throughout Byron's oeuvre .